Structural and functional bases of visuospatial associative memory in older adults - Zamboni, G; Zamboni, G; de Jager, C; Drazich, E; Douaud, G; Jenkinson, M; Smith, A; Smith, A; Tracey, I; Wilcock, G (2013)
Impaired visuospatial associative memory may be one of the earliest changes predicting cognitive impairment and Alzheimers disease. We explored the relationship between performance on a visuospatial associative memory task (the Placing Test) and brain structure and function in cognitively healthy older adults. First, we performed a voxel-based morphometry correlational analysis on structural magnetic resonance imaging (MRI) data from 144 healthy older adults with their scores on the Placing Test. Second, we carried out a functional MRI study on another group of 28 healthy older adults who performed a similar task during functional MRI. Decreased performance on the Placing Test was associated with increased atrophy in medial-temporal regions. Functional activation of the same regionscontrolling for the effect of atrophyoccurred during successful performance of the same task. The colocalization of structural and functional MRI correspondents of visuospatial associative test performance within medial-temporal regions validates multimodal imaging in describing behaviorally relevant variability in the aging brain and suggests that the Placing Test has the potential for detecting early cognitive changes occurring in preclinical phases of Alzheimer's disease. © 2013 Elsevier Inc.